ANALISIS GAYA BELAJAR PESERTA DIDIK SEBAGAI DASAR PENYUSUNAN PROGAM BELAJAR KELAS VIII - Iskandar, Abdul Muis; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbsractLearning style is the way that selected learners tend to react and use stimulants-stimulant in absorbing and then organize and manipulate information on the learning process. For a teacher knows the style of learning each learner is the important thing because it can be in the set as reference in selecting the style of teaching that is appropriate. Common problems of the research is "how learning style On Learners Learning Program as the basis for the preparation of Class VIII SMP Negeri Pontianak 8 Years 2017/2018?". The general objective of this research is to obtain the information clearly and objectively about the analysis of learning styles On the learners as the basis for the preparation of the Program of classes VIII SMP Negeri Pontianak 8 Years 2017/2018. Based on the results of this in peneltian conclude that: (1) learning styles the visual learner class VIII belongs to "good" (2) auditory learners learning style class VIII belongs to "good" (3) learning style kinesthetic learners class VIII belongs to "enough" (4) Tutoring Programs in accordance with learning style students of class VIII i.e. program drawn up in accordance with learning style learners. Kata Kunci           : Learning Style, Learners